Clinical outcome of bi-unicompartmental knee arthroplasty for both medial and lateral femorotibial arthritis: a systematic review-is there proof of concept? - Wada, K; Price, A; Gromov, K; Lustig, S; Troelsen, A (Springer, 2020)
Introduction: Unicompartmental knee arthroplasty (UKA) is a well-accepted treatment for isolated unicompartmental osteoarthritis (OA) of the knee. In previous literature, it has been suggested that bi-unicompartmental knee arthroplasty (bi-UKA) which uses two UKA implants in both the medial and lateral compartments of the same knee is a feasible and viable option for the treatment of knee OA. Given the advantages of UKA treatment, it is warranted to review the literature of bi-UKA and discuss the evidence in terms of implant selection, indications, surgical techniques, and outcomes, respectively.